Student identity, writing anxiety, and writing performance: a correlational study - DeDeyn, Rachel Ryan, author; Flahive, Douglas, advisor; Ehlers-Zavala, Fabiola, committee member; Swaim, Randall C., committee member (Colorado State University. Libraries, 2011)
While identity research has recently become popular in the field of language acquisition, most of the research conducted in this area has been qualitative in nature. Possibly due to the lack of quantitative identity research, few language acquisition studies have attempted to find relationships between identity and other individual differences. The purpose of this study is to fill these gaps in the literature by answering the questions: 1) Is there a relationship between student identity, writing anxiety, and writing performance? and 2) What is the nature of this relationship if it exists? Participants in this study were 33 international undergraduate students of advanced English proficiency enrolled in an introductory university writing course. This study defines student identity as the degree of student integration into the culture of an American university. This construct was measured through participant responses to open ended journaling prompts about their educational experiences in their home country and in the United States. These qualitative responses were read and scored by four raters, converting the data to a single, quantitative score for each participant. Writing anxiety was measured with the Second Language Writing Anxiety Inventory (SLWAI) and writing performance was measured with the scores participants earned on the papers submitted for their writing class. The linear relationships between these variables were explored through correlations. Inverse relationships were found between student cultural integration and writing performance and between student cultural integration and writing anxiety for students who showed changes in writing performance over the course of the semester. The implications of these findings, limitations of this study, and suggestions for future research are considered.
Keywords: acculturation; writing; performance; identity; anxiety